SOCIO-ECONOMIC DAMAGE BY ACUTE CORONARY SYNDROME IN RUSSIAN FEDERATION - A. V. Kontsevaya; A. M. Kalinina; I. E. Koltunov; R. G. Oganov (Столичная издательская компания, 2016)
Aim. To estimate the economic damage by acute coronary syndrome (ACS) in Russia in 2006-2009. Material and Methods. Direct costs and economic losses associated with ACS were estimated. The structure of direct costs includes the costs of hospitalization, medical emergencies, out-patient visits, high-tech medical care, as well as drug therapy in outpatient treatment. Losses in the economy associated with ACS include loss of gross domestic product due to death in working-age, temporary disability and payments of disability benefits. Estimation of economic damage by cardio-vascular diseases was based on analysis of Russian Ministry of Health official statistics. Results. Approximately 520,000 cases of ACS are registered annually (36,4% - myocardial infarction, 63,6% - unstable angina). Trend to increased mortality from myocardial infarction, especially among women, was found during the analyzed period. From 2000 to 2009 this index rose from 34.9 to 41.1 per 100,000 of population among women, and from 52.3 to 55.9 per 100,000 of population among men. Total direct costs of health care for patients with ACS in 2009 amounted to almost 21 billion rubles, and indirect - 53.5 billion rubles. The total economic damage by ACS in Russia in 2008-2009 exceeded 70 billion rubles per year. Conclusion. ACS in Russia is connected with significant social and economic damage. Most part of this damage is indirect losses in economy due to premature mortality of working aged men.